Quantitative analysis of the effect of ocular rotation on postoperative residual astigmatism in small incision lenticule extraction for myopia correction - Liu, Caiyu; Xu, Xiaoying; Gu, Hao; Wang, Chi; Lu, Lu; Ye, Kaizhen; Zheng, Yan; Wang, Haiyan; Chen, Wei; Li, Meiyan; Zhou, Xiaolin; Ou, Shangkun; et al. (Frontiers in Cell and Developmental Biology, 2025)
ObjectiveThe aim of this study was to conduct a systematic investigation into the effects of ocular rotation on postoperative residual astigmatism in patients undergoing small incision lenticule extraction (SMILE).MethodsA prospective observational cohort study involved 79 patients (153 eyes) with myopia and astigmatism who underwent SMILE surgery. Ocular rotational magnitude was measured using manual corneal and scleral marking with a slit-lamp microscopy assessment. Preoperative and postoperative (1- and 3-month) assessments included uncorrected distance visual acuity (UDVA), best-corrected visual acuity (BCVA), refractive error, and other relevant ocular parameters.ResultsResidual astigmatism showed significant correlations with ocular rotation magnitude (r = 0.429, p < 0.001), preoperative intraocular pressure (r = −0.178, p = 0.032), and preoperative cylindrical lens power (r = 0.175, p = 0.035). A multiple linear regression analysis indicated that rotation magnitude significantly impacted postoperative residual astigmatism (p < 0.001). However, preoperative intraocular pressure (p = 0.349) and spherical equivalent (p = 0.105) were not significantly related to residual astigmatism. Linear regression analysis further demonstrated significant positive correlations between rotation amplitude and various astigmatism parameters at both 1- and 3-month postoperative follow-ups (all p < 0.05). In particular, the relationships were quantified as follows: cylindrical lens (CYL [D]) (1 month: y = 7.058x + 17.480, p < 0.001; 3 months: y = 7.464x + 13.610, p < 0.001), target-induced astigmatism (TIA [D]) (1 month: y = 0.112x + 1.275, p = 0.012; 3 months: y = 0.097x + 1.217, p = 0.026), surgically induced astigmatism (SIA [D]) (1 month: y = 0.094x + 0.936, p < 0.001; 3 months: y = 0.059x + 0.911, p = 0.022), and difference vector (DV [D]) (1 month: y = 0.041x + 0.289, p = 0.005; 3 months: y = 0.037x + 0.866, p = 0.011). Notably, rotation amplitude exhibited the strongest association with postoperative CYL. Receiver operating characteristic (ROC) analysis determined the optimal thresholds for rotation magnitude in predicting residual astigmatism to be 1.5° at 1 month (AUC = 0.753; sensitivity 79.7%; specificity 58.2%) and 2.5° at 3 months (AUC = 0.929; sensitivity 92.9%; specificity 83.5%).ConclusionThe magnitude of rotation shows a notably positive correlation with residual astigmatism during both the 1- and 3-month postoperative follow-ups. Thresholds of 1.5° (1 month) or 2.5° (3 months) prove predictive of residual astigmatism, with enhanced diagnostic precision at the later follow-up.